1998
DOI: 10.1159/000016133
|View full text |Cite
|
Sign up to set email alerts
|

Explorative Study of Costs, Effects and Savings of Screening for Female Fragile X Premutation and Full Mutation Carriers in the General Population

Abstract: Objective: Evaluation of the costs, effects and savings of three strategies for female fragile X premutation and full mutation carrier screening in the general population. Methods: We calculated the costs, effects and savings by using a general model for prenatal, preconceptional, and school carrier screening. Assumptions were based on literature data, expert opinions, prices and tariffs. Results: Prenatal screening will detect most carriers and will lead to the highest number of avoided fragile X syndrome pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…G Pembrey and co-workers 2 provided a descriptive framework for different strategies, and recommended a 5-year programme of active case finding and cascade screening in the UK. G Wildhagen and co-workers 8 developed a decision analytic model to compare prenatal, preconceptual and school screening for FXS in The Netherlands. They found that all strategies have a favourable cost-saving balance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…G Pembrey and co-workers 2 provided a descriptive framework for different strategies, and recommended a 5-year programme of active case finding and cascade screening in the UK. G Wildhagen and co-workers 8 developed a decision analytic model to compare prenatal, preconceptual and school screening for FXS in The Netherlands. They found that all strategies have a favourable cost-saving balance.…”
Section: Discussionmentioning
confidence: 99%
“…During the first 10 years, the estimated direct cost per year to the NHS in England and Wales is £0.7-0.2 million by active cascade screening and £14. [5][6][7][8][9].1 million by a programme of prenatal screening. The incremental cost per extra carrier detected (using current practice as the reference standard) is on average only £165 (range: £129-182) by active cascade screening and £7543 (range: £5316-14,636) by prenatal screening.…”
Section: Findings Of the Fxs Modelmentioning
confidence: 99%
See 3 more Smart Citations